Kearifan Lokal Masyarakat Dalam Mengelola Ikan Bilih di Nagari Muaro Pingai Kecamatan Junjung Sirih Kabupaten Solok - Sertika Wahyuni; Nefilinda Nefilinda; Rika Despica (Departement of Mathematics Education, 2023)
This research is motivated by community problems in managing bilih fish. Bilih fish is one of the local potentials owned by the West Sumatra region, it lives in Lake Singkarak which is located between two regencies in West Sumatra, namely Solok Regency and Tanah Datar Regency. The purpose of this study is to analyze and describe 1) the form of local wisdom in catching bilih fish 2) How the form of processing bilih fish 3) the form of preserving bilih fish. The type of research used is qualitative informant research, namely a number of objects that will be examined or taken and made into parameters in collecting informant data that can provide information and data needed in research. Research informants were taken by Snowball Sampling, namely the technique of determining a sample that was initially small in number and then enlarged. The research results obtained: 1) Forms of Local Wisdom Catching bilih fish in Nagari Muaro Pingai found tools used to catch fish using traditional tools in the form of tools such as nets (trawl / nets) the size of which is set at 1 inch so that people do not catch fish that are still small in size . The tradition of the ancestors when catching bilih fish is by tapping the water 3 times and the best time to catch bilih fish is in the afternoon until evening. 2) Forms of processing bilih fish in Nagari Muaro Pingai include processed dried fish and processed wet fish. 3) the form of local wisdom on the preservation of bilih fish in Nagari Muaro Pingai PERNAG (Nagari Regulation) regarding the prohibition of fishing using explosives, electric shock (electricity) and toxic chemicals in the lake. In fact, to maintain the sustainability of the fish population, namely by making FADs in the waters of Lake Singkarak which serves as a place for fish to rest and lay their eggs.